2011
DOI: 10.1111/j.1440-1789.2010.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological impairments in microglia precede age-related neuronal degeneration in senescence-accelerated mice

Abstract: The ageing brain is characterized by degenerative changes in both neurons and glia. Although neurons are known to lose dendritic complexity with ageing, age-related changes in the morphology of microglia have not been well documented. We investigated potential age-related changes in microglial morphology using mouse models. Senescence-accelerated mouse prone 10 (SAMP10) in which neuronal degeneration begins to appear around 8 months of age and becomes progressively remarkable with advancing age was used as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Given that microglia are neuroprotective, it is reasonable to consider that aging-related, progressive microglial degeneration, and loss of microglial neuroprotection rather than induction of microglial activation contributes to the onset of sporadic AD (86). This idea is also supported by our own findings on microglial aging in SAMP10 mice (87). …”
Section: Clinical Relevance Of Basic Studies Of the Structure And Funsupporting
confidence: 81%
“…Given that microglia are neuroprotective, it is reasonable to consider that aging-related, progressive microglial degeneration, and loss of microglial neuroprotection rather than induction of microglial activation contributes to the onset of sporadic AD (86). This idea is also supported by our own findings on microglial aging in SAMP10 mice (87). …”
Section: Clinical Relevance Of Basic Studies Of the Structure And Funsupporting
confidence: 81%
“…As such microglia priming is considered an important confounding factor in age-associated neurodegenerative diseases [79, 80]. On the other hand, dystrophic microglia, characterized by loss of structural integrity, presence of spheroid inclusions and fragmented cellular processes have been reported in the aged human brain [81] or in rodent mouse models of accelerated aging and neurodegeneration [82, 83]. Since dystrophy in microglia is restricted to aged and neurodegenerative brain tissues, it has been proposed to be the consequence of age-associated telomere shortening and replicative senescence in microglia [36].…”
Section: Discussionmentioning
confidence: 99%
“…According to the former studies about microglial cells morphology in age-related disease, researchers have observed that microglia become activated in aged rats (Ogura et al, 1994;Kawamata et al, 1998). Quantitative analysis has shown that abnormalities of microglia in the early stage may cause the SAMP10 mice vulnerable to age-related neuronal degeneration (Hasegawa-Ishii et al, 2011). Iba-1, a marker of microglial activation (Ahmed et al, 2007), was evaluated in this paper; the results showed that K-PS low significantly downregulated the expression of Iba-1 which indicated that activated microglial cells were inhibited to a certain extent.…”
Section: Discussionmentioning
confidence: 99%